2011
DOI: 10.1371/journal.pone.0019610
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Chemistry in Protein Remodeling at the Cell-Material Interface

Abstract: BackgroundThe cell-material interaction is a complex bi-directional and dynamic process that mimics to a certain extent the natural interactions of cells with the extracellular matrix. Cells tend to adhere and rearrange adsorbed extracellular matrix (ECM) proteins on the material surface in a fibril-like pattern. Afterwards, the ECM undergoes proteolytic degradation, which is a mechanism for the removal of the excess ECM usually approximated with remodeling. ECM remodeling is a dynamic process that consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
61
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 70 publications
7
61
4
3
Order By: Relevance
“…Furthermore, we noted that the hydrophobic/hydrophilic characteristics of the surface alter FA maturation. In fact, as reported by Llopis-Hernández et al [27], FA formation is enhanced on more hydrophilic surfaces, because there is an increased availability of binding domains of the physisorbed protein layer. Indeed, we found that on oxygen PT surfaces FAs are longer and wider and can reach a length of up to 13 mm (figure 8f ).…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, we noted that the hydrophobic/hydrophilic characteristics of the surface alter FA maturation. In fact, as reported by Llopis-Hernández et al [27], FA formation is enhanced on more hydrophilic surfaces, because there is an increased availability of binding domains of the physisorbed protein layer. Indeed, we found that on oxygen PT surfaces FAs are longer and wider and can reach a length of up to 13 mm (figure 8f ).…”
Section: Discussionsupporting
confidence: 51%
“…This increased area in the surface modified titanium discs could be coupled to a higher protein adsorption coming from the serum of the cell culture medium. Protein adsorption and matrix remodelling at the cell-material interface has been previously described as a potent cell adhesion inductor 44) . Other previous works are also in concordance with our adhesion and proliferation results 28,45) .…”
Section: Discussionmentioning
confidence: 99%
“…Role of Fn and Vn in cell adhesion on material surfaces has been extensively studied using polymer substrates [11][12][13][14][15][16] and SAMs [17][18][19][20][21][22]. Pretreatment of artificial materials with a solution containing either Fn only or Vn only improves http://dx.doi.org/10.1016/j.actbio.2015.08.033 1742-7061/Ó 2015 Acta Materialia Inc.…”
Section: Introductionmentioning
confidence: 99%